The Relevance of Using Social Media Applications Strategies to Increase Marketing Potential of Indonesian Maritime Tourism (Analytical Study of Tourism Journals and Online Marketing) - Surya Fadjar Boediman; Prasetyono Hendriarto; Nugroho Djati Satmoko; Sulistiyani Sulistiyani; Amar Sani (Budapest International Research and Critics University, 2021)
This literature analysis aims to understand the relevance of social media applications as a marketing strategy for Indonesian tourist destinations in the virtual era. As technology advances, all businesses are involved in technology. One of them is using social media applications as a strategy in marketing tourist destinations in a country. In order to understand how relevant social media applications are to tourism destination marketing, we have collected evidence from previous studies and then analyzed them by involving an in-depth evaluation and interpretation coding system so that we can understand the relevance of the two variables above. Our data search is done electronically on databases of several international publications such as search, Taylor and Francis, Google books, several other publications. Based on the study and discussion results, we understand that social media applications are very relevant in providing information and promoting various tourist destinations in Indonesia, which are well-known tourist destinations. Thus, this finding is hoped to continue obtaining data for academic purposes and other business applications